Postural balance following aerobic fatigue tests: A longitudinal study among young athletes - Steinberg, N.; Eliakim, A.; Zaav, A.; Pantanowitz, M.; Halumi, M.; Eisenstein, T.; Meckel, Y.; Nemet, D. (Journal of Motor Behavior, 2016)
General fatigue can cause aggravation of postural balance, with increased risk for injuries. The present longitudinal study aimed to evaluate the postural balance of young athletes following field aerobic tests throughout 1 year of training. Thirty children from a sports center in Nazareth, participating in a 3 times/week training program (specific to basketball, soccer, or athletic training), were assessed. Postural balance parameters were taken before, immediately after, and 10 min after a 20 m shuttle-run aerobic test, at 3 time points during 1 training year (Start/Y, Mid/Y, and End/Y). Fitness improved at the Mid/Y and End/Y compared to Start/Y. Postural balance significantly deteriorated immediately after the aerobic test and improved significantly in the 10-min testing in all 3 time points, with significant deterioration in the End/Y compared with the Start/Y. In conclusions, postural balance deteriorates immediately after aerobic exercises, and at the end of the year. To better practice drills related to postural balance and possibly to prevent injuries, it is best for young athletes to properly rest immediately following aerobic exercises and to practice postural balance mainly at the beginning and at the middle of the training year. ABSTRACT FROM AUTHOR